2005
DOI: 10.1111/j.1600-079x.2005.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on the thermoregulatory responses to intermittent exercise

Abstract: We examined the effects of a single 2.5-mg dose of melatonin on the thermoregulatory and circulatory responses to intermittent exercise at a room temperature of 27.2+/-0.4 degrees C (mean+/-S.D.), a relative humidity of 55+/-3% (mean+/-S.D.), and a light intensity of 200-300 lux. In a double-blind cross-over study, six male participants ingested either melatonin or placebo at 11:45 hr. Participants then rested in a semi-supine position for 75 min and completed an intermittent running protocol for 66 min at alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 34 publications
4
39
2
3
Order By: Relevance
“…Hill et al (1992) in their study they confirm the time of day effect of anaerobic capacity [8]. The results of our study were similar to the results of Atkinson and Reilly (1996) and [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…Hill et al (1992) in their study they confirm the time of day effect of anaerobic capacity [8]. The results of our study were similar to the results of Atkinson and Reilly (1996) and [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it can be postulated that the rise in melatonin levels after exercise during the current study may be brought about via postganglionic b 1 adrenergic receptors (Vaughan and Reiter 1987). This rise in melatonin with exercise is similar to the elevations seen when an acute dose of exogenous melatonin is administered (Atkinson et al 2005a, b;Harris et al 2001). However, studies that have utilised an exogenous melatonin have produced equivocal findings in terms of heart rate responses.…”
Section: Discussionmentioning
confidence: 50%
“…However, studies that have utilised an exogenous melatonin have produced equivocal findings in terms of heart rate responses. Harris et al (2001) and Atkinson et al (2005a) found decreases in heart rate following administration of melatonin during the daytime. However, Atkinson et al (2005b) conversely found that heart rate was not altered by ingestion of melatonin.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Jones (15) showed that MEL administration (5 mg) at 11:45 h affected choice reaction time, subjective alertness, short-term memory measured both at 13:00 h and 15:00 h. These results confirm the present study findings observed at 08:00 h. It seems that daytime MEL ingestion could affect cognitive performances and exert a hypnotic effect if it is very close to the evaluation. Furthermore, Atkinson et al (5) showed that the diurnal ingestion of a lower dose of MEL (2.5 mg) at 11:45 h did not influence the subjective alertness and sleep before and after exercise done 75 min after MEL administration. Consequently, to assure that MEL does not affect the cognitive responses, it seems necessary to rise the duration between time of ingestion and the evaluation session.…”
Section: Discussionmentioning
confidence: 99%
“…MEL, often considered as a chronobiotic (12), was initially investigated in terms of its role in endocrine physiology regulating circadian and sometimes seasonal rhythms (22). Moreover, it has been shown that exogenous MEL can improve sleep quality and alleviate jet lag symptoms after transmeridian travels (5). In addition to the control of the biological rhythms, it is known that exogenous MEL administration has clear hypothermic effects (10).…”
mentioning
confidence: 99%